1981
DOI: 10.1128/jvi.39.2.438-446.1981
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to two glycoproteins of herpes simplex virus type 2

Abstract: Monoclonal antibodies to herpes simplex virus type 2 were found to precipitate different numbers of radiolabeled polypeptides from lysates of virus-infected cells. Antibodies directed against two viral glycoproteins were characterized. Antibodies from hybridoma 17aA2 precipitated a 60,000-molecular-weight polypeptide which chased into a 66,000and a 79,000-molecular-weight polypeptide. All three polypeptides labeled in the presence of [3H]glucosamine and had similar tryptic digest maps. The 60,000-molecular-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
1

Year Published

1982
1982
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 24 publications
(21 reference statements)
1
42
1
Order By: Relevance
“…Herpes simplex viruses specify a number of glycoproteins (2,3,8,9,21,24) which are located on the virion envelope as well as on the surface of infected cells. These glycoproteins have been termed "social" proteins (14) since they mediate interactions between virions and host cells (24,26,27), between infected cells (11,19), and between various components of the immune system and virions or infected cells (15,23,26,27).…”
mentioning
confidence: 99%
“…Herpes simplex viruses specify a number of glycoproteins (2,3,8,9,21,24) which are located on the virion envelope as well as on the surface of infected cells. These glycoproteins have been termed "social" proteins (14) since they mediate interactions between virions and host cells (24,26,27), between infected cells (11,19), and between various components of the immune system and virions or infected cells (15,23,26,27).…”
mentioning
confidence: 99%
“…The kinetics of appearance of both gC-1 and gC2 in infected cells showed that the proteins could only be clearly detected in cells labeled 3 to 5 h postinfection and not in the presence of DNA synthesis inhibitors, whereas other glycoproteins could be detected as early as 1 to 3 h postinfection (3,26). gC is present on the membrane of HSV-infected cells (3,23,44) as well as on the virion surface (44).…”
mentioning
confidence: 98%
“…In another study with intertypic recombinant viruses (20), an HSV-2 glycoprotein of 63,000 daltons with no apparent HSV-1 counterpart was mapped between 0.55 and 0.65 m.u. Monoclonal antibodies (MABs) to HSV-2 glycoproteins also detected a small glycoprotein with a molecular weight of 60,000 which could be chased into higher-molecular-weight forms of 66,000 and 79,000 (3,4) and was designated gF. Results from two studies with monoclonal antibodies (44,45) showed that HSV-2 gF shared antigenic determinants with HSV-1 gC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Monoelonal antibodies to HSV-1 are able to recognize specific individual proteins (3,4) and glycopioteitis (3)(4)(5)(6)(7)(8)(9) as shown by radioitntnuiioptecipitation and polyaerylamide gel eleetrophoresis. Similarly, immunolluorescent staining has been applied to demonstrate the existence of speeific antigens in infected cells and some reports have documented the locations of particular proteins (4,9,10).…”
mentioning
confidence: 99%